The active heroin metabolite 6-acetylmorphine has robust reinforcing effects as assessed by self-administration in the rat. (15th May 2019) - Avvisati, Riccardo; Bogen, Inger Lise; Andersen, Jannike M.; Vindenes, Vigdis; Mørland, Jørg; Badiani, Aldo; Boix, Fernando
Abstract: Previous studies have suggested that at least some of the behavioral effects of heroin might be mediated by its active metabolite 6-acetylmorphine (6-AM). The aim of the present study was to investigate the reinforcing effects of 6-AM and its role in mediating those of heroin. We used an intravenous self-administration procedure in male Sprague-Dawley rats including four phases: acquisition, extinction, reinstatement of drug-seeking, and re-acquisition. Independent groups of rats readily learned to self-administer equimolar doses (0.135 μmol/kg) of either 6-AM (44.3 μg/kg) or heroin (50 μg/kg). Under a fixed ratio 1 (FR1) schedule of reinforcement, the rate of responding was the same for 6-AM and heroin, but it was significantly higher for 6-AM than for heroin under a FR2 schedule. A non-contingent infusion ('priming') of 0.068 μmol/kg of either 6-AM or heroin reinstated non-reinforced drug-seeking (relapse). The rats readily re-acquired self-administration behaviour when given access to one of two doses (0.068 and 0.135 μmol/kg) of 6-AM or heroin. Pretreatment with a specific monoclonal antibody (mAb) against 6-AM blocked the priming effect of 6-AM, and modified the rate of lever-pressing on re-acquisition of 6-AM self-administration in a manner compatible with a shift to the right of the dose-effect curve. The mAb did not affect heroin responding. The present results show that 6-AM possesses reinforcing effects similar to those of heroin. The lack of effect of 6-AM mAb on heroin priming and heroin self-administration calls for further studies to clarify the role of heroin and its metabolites in heroin reward. This article is part of the Special Issue entitled 'New Vistas in Opioid Pharmacology'. Highlights: Heroin metabolizes very fast in the blood to active 6-acetylmorphine (6-AM). 6-AM sustains self-administration behavior in the rat similarly to heroin. Thus, 6-AM possesses reinforcing properties similar to those of heroin. Blockade of 6-AM in the blood by a mAb do not affect heroin self-administration. 6-AM from heroin breakdown in the brain can be enough to uphold self-administration.